Assessing early child development and its association with stunting and schistosome infections in rural Zimbabwean children using the Griffiths Scales of Child Development - Francisca Mutapi; Lorraine Pfavayi; Derick Osakunor; Rivka Lim; Maritha Kasambala; Arnold Mutemeri; Simbarashe Rusakaniko; Dixon Chibanda; Takafira Mduluza (Public Library of Science (PLoS), 2021)
There is a paucity of reference early childhood development (ECD) data at community level in rural Africa. Our objective was to conduct a comprehensive assessment of ECD in rural Zimbabwe and determine the impact of stunting and schistosome infections on ECD. Using the Griffiths Scales of Child Development, we conducted a cross sectional assessment of Eye and Hand Coordination (EHC), Personal-Social-Emotional (PSE), Language and Communication (LC), Foundations of Learning (FL) and Gross Motor (GM) domains and the summary General Development (GD) in 166 children aged 6-72 months. The effects of stunting, malnutrition and Schistosoma haematobium infection on ECD was determined. The impact of praziquantel curative treatment of schistosome infection on the developmental scores was determined through a longitudinal follow up at 6 and 12 months. From an initial 166 children, 11 were found to have developmental deficits warranting further investigation. Of the remaining 155, 58.7% recorded a good (≥ average) score for the overall General Development (GD). Proportions of children scoring above the cut-off (≥ average) for each domain were GM (84.5%), PSE (80.6%), EHC (61.9%), FL (43.9%) and LC (44.5%). The prevalence of stunting was 26.8% (95% CI = 20.1%-34.8%) Scores for stunted children were significantly lower for EHC (p = 0.0042), GM (p = 0.0099), and GD (p = 0.0014) with the fraction of lower scores attributable to stunting being GM = 63.4%, GD = 46.6%, EHC = 45%, and LC = 21%. S. haematobium infection prevalence was 39.7% and mean infection intensity was 5.4 eggs/10 ml urine. Infected children had poorer cognitive performance scores for the FL (p = 0.0005) with 30.8% of poor FL attributable to the infection. Performance in all domains improved to the expected normal or above reference levels at 6 and 12 months post curative treatment of schistosome infections. Our study documented reference values for ECD in rural Zimbabwean children. The study detected deficiencies in the FL domain, which were more pronounced in children, infected with schistosomes, highlighting the need for provision of cognitive stimulation tools and access to early childhood foundation education. There is also need for improved child nutrition and treatment of schistosome infections to improve child development outcomes. Author summary There is a paucity of comprehensive early childhood development data at community level in rural Africa. We assessed the development of rural Zimbabwean children aged 6-72 months and determined the impact of stunting and schistosome infections on their 5 developmental domains; Eye and Hand Coordination, Personal-Social-Emotional, Language and Communication, Foundations of Learning and Gross Motor domains and the summary General Development. We have demonstrated that just over 50% of Zimbabwean children in rural areas are on course for normal child development; with many being more advanced for their age in Gross Motor and Personal-Social-Emotional domains. We also demonstrate that the children face developmental challenges in early childhood, particularly in Foundations for Learning which represents critical psychometric constructs and cognitive skills for learning, executive function, ways of thinking, problem solving, organizing and information planning, analytic thought and memory. We further demonstrate that the poor development scores especially in Foundations for Learning were also attributable to stunting and schistosome infection, with the impact of the latter being reversed by curative antihelminthic treatment. Taken together, the findings strengthen the call for the treatment of paediatric schistosomiasis, accessibility to cognitive stimulation tools and improved nutrition to improve childhood health outcomes.